Tobacco advertisement, promotion and sponsorship ban enforcement index at sales points in Panama, 2017 - Víctor Hugo Herrera (Tobacco Induced Diseases, 2019)
Introduction We assess the tobacco advertisement, promotion and sponsorship (TAPS) ban enforcement in sales points in Panama in 2017.